2021
DOI: 10.1016/j.bbrc.2021.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of CT-P59 against SARS-CoV-2 South African variant

Abstract: The global circulation of newly emerging variants of SARS-CoV-2 is a new threat to public health due to their increased transmissibility and immune evasion. Moreover, currently available vaccines and therapeutic antibodies were shown to be less effective against new variants, in particular, the South African (SA) variant, termed 501Y.V2 or B.1.351. To assess the efficacy of the CT-P59 monoclonal antibody against the SA variant, we sought to perform as in vitro binding and neutralization … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…The CT-P59 human monoclonal antibody (Regdanvimab) specifically binds to spike of SARS-CoV-2, blocking interaction with ACE2 for viral entry. We have demonstrated that CT-P59 has neutralization and protection against the original and Beta viruses in in vitro and in vivo studies [ 16 , 17 ]. However, it remains uncertain whether CT-P59 has the therapeutic effect on Gamma, Delta and its associated variants.…”
Section: Introductionmentioning
confidence: 99%
“…The CT-P59 human monoclonal antibody (Regdanvimab) specifically binds to spike of SARS-CoV-2, blocking interaction with ACE2 for viral entry. We have demonstrated that CT-P59 has neutralization and protection against the original and Beta viruses in in vitro and in vivo studies [ 16 , 17 ]. However, it remains uncertain whether CT-P59 has the therapeutic effect on Gamma, Delta and its associated variants.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in vivo ferret challenge studies demonstrated that a therapeutic dosage of CT-P59 decreased upper and lower respiratory tract viral load of the beta (“South African”) variant, termed B.1.351 (K417N/E484K/N501Y), to a comparable extent as that observed with the wild-type virus. 19 The finding of sufficient antiviral effect in B.1.351-infected animals treated with a clinical dosage of CT-P59 suggests that CT-P59 has therapeutic potential for patients infected with the beta variant of SARS-CoV-2. 19 …”
Section: Discussionmentioning
confidence: 99%
“… 19 The finding of sufficient antiviral effect in B.1.351-infected animals treated with a clinical dosage of CT-P59 suggests that CT-P59 has therapeutic potential for patients infected with the beta variant of SARS-CoV-2. 19 …”
Section: Discussionmentioning
confidence: 99%
“…In the past, animal models have successfully substituted for human hosts to study the within-host dynamics of many viruses, such as HIV, HCV, and HBV [ 13 , 14 , 15 , 16 , 17 ]. In particular, respiratory viruses that infect humans have been widely studied using ferrets [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], and recent studies have shown that SARS-CoV-2 can successfully transmit and replicate in ferrets [ 1 , 27 , 28 , 29 , 30 , 31 ]. As in previous studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], mathematical models fit to data from animals can be a powerful tool to characterize within-host viral kinetics of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have provided important insights into the viral dynamics [ 40 , 42 , 43 , 44 ], immune responses [ 8 , 9 , 45 ], and potential antiviral therapy [ 41 , 48 ] within human hosts [ 8 , 9 , 40 , 41 , 42 , 44 , 45 ] and macaques [ 40 , 43 ], many aspects of within-host dynamics still remain uncertain. Furthermore, most of the data used in these studies were obtained post-symptom onset, and none of these models dealt with the dynamics within the ferret, which has been considered one of the important animal models for experimental studies of SARS-CoV-2 [ 1 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%